Precipitates in Additively Manufactured Inconel 625 Superalloy - Dubiel, Beata (Materials (Basel), 2019)
Laser-based additive manufacturing processes are increasingly used for fabricating components made of nickel-based superalloys. The microstructure development, and in particular the precipitation of secondary phases, is of great importance for the properties of additively manufactured nickel-based superalloys. This paper summarizes the literature data on the microstructure of Inconel 625 superalloy manufactured using laser-based powder-bed fusion and directed energy deposition processes, with particular emphasis on the phase identification of precipitates. The microstructure of Inconel 625 manufactured by laser-based directed energy deposition in as-built condition is investigated by means of light microscopy and transmission electron microscopy. Phase analysis of precipitates is performed by the combination of selected area electron diffraction and microanalysis of chemical composition. Precipitates present in the interdendritic areas of as-built Inconel 625 are identified as MC and M(23)C(6) carbides as well as the Laves phase.